Vegetarianism in Food-Based Dietary Guidelines - Luciana Baroni (International Journal of Nutrition, 2015)
Plant foods are staples of many cultures in the world. Conversely, the appearance of vegetarianism in Western countries is a relatively recent phenomenon, showing an upward trend: people following vegetarian diets (both lacto-ovo-vegetarian-LOV and vegan-VEG), account today for about 10% of the Western population. According to the principle of non-discrimination, the most recent national dietary guidelines for the general population (DGLs) of some Western countries have adapted their contents to comprise vegetarian eating patterns. Moreover, since 1997, specific vegetarian food guidelines (VFGs) were developed. The aim of this review was to summarize and compare the information and recommendations of the food-based dietary guidelines (FBDGs) contained in the DGLs usable by vegetarians, and in the main VFGs; to extract a list of basic criteria for the planning of a well-balanced vegetarian diet, and to identify the most valid FBDG for vegetarians. An Internet search was conducted in the English language, in order to identify national DGLs applicable to vegetarian dietary patterns, and international VFGs. Four Western DGLs and six VFGs were selected. Compared to the majority of DGLs, VFGs are not an
Keywords: vegetarian nutrition